GAYA BAHASA DAN PESAN-PESAN PADA LIRIK LAGU EFEK RUMAH KACA BERJUDUL “MERAH” - Muhamad Syamsul Arifin; Edwin Purbo Saputro; Teti Sobari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This article aims to analyze the style of the language used and the messages conveyed in the lyrics of the song Efek Rumah Kaca titled Merah. The method used in this study is descriptive qualitative method which means that the research analyzing data and the results of the data in the form of description. Based on the results of the analysis, there are comparative language styles (metaphors and depersonalizations), the style of the linking language (euphemism), the language style of contradiction (paradox), and the language style of iteration (assonances and epistrofa). The messages contained in this song is the condition of Indonesian politics, the attitudes of people to the political condition, and hope also the invitation of the struggle for politics in Indonesia to improve.